Producing knowledge about tropical fevers in the andes: Preventive inoculations and yellow fever in Colombia, 1880-1890 (2012)
This paper analyses the emergence of yellow fever as a distinct disease in Colombia in the 1880s. Originally considered a variety of periodic paludic fever, confined to coastlines and warm river valleys, yellow fever was redefined by Colombian doctors over a period of less than ten years, as a distinct non-paludic, fever, which could occur in temperate lands and which was caused by a micro-organism. Two phenomena were fundamental in this shift: the unexpected outbreaks of paludic-like fevers in highland and inland areas, and the controversy surrounding the Pasteurian practice of the preventive inoculations of germs. This case study sheds light on the way medical knowledge is produced in a particular locality. © 2012 The Author.